Sistema fluxo-batelada monossegmentado: determinação espectrofotométrica de boro em plantas. - Barreto, Inakã Silva (2012)
This work introduces the monosegmented flow-batch (MSFB) analysis concept. This system combines favourable characteristics of both flowbatch and the monosegmented analysers, allowing use of the flow-batch system for slow reaction kinetics without impairing sensitivity or sampling throughput. The MSFB was evaluated during spectrophotometric determination of boron in plant extracts, which is a method that involves a slow reaction between boron and azomethine-H. All standard solutions were prepared in-line, and all analytical processes completed by simply changing the operational parameters in the MSFB control software. The limit of detection was estimated at 0.008 mg L−1. The measurements could be performed at a rate of 120 samples per hour with satisfactory precision. The proposed MSFB was successfully applied to analyse 10 plant samples and the results are in agreement with the reference method at a 95% level of confidence.